CORPORATE GOVERNANCE, KUALITAS AUDIT, DAN KECENDERUNGAN PRAKTIK TAX AVOIDANCE - Nanik Niandari; Fitria Nur Afni; Handayan Handayan (Jurnal Solusi, 2021)
This study aims to examine the effect of Corporate Governance (CG) on tax avoidance. This research was conducted using manufacturing companies listed on the IDX in the 2015-2019 period. Total sample used was 179 companies with total of 498 observations. The sampling method used was purposive sampling and data was analysed with multiple linear regression. Tax avoidance as dependent variable is measured by Effectice Tax Rate. Independent variables used in this research are corporate governance and audit quality. Corporate Governance as independent variable is measured by the proportion of independent commissioners, institutional ownership, and audit committee. The result shows that the variable proportion of independent commissioners has a significant positive effect, institutional ownership has a significant negative effect, and the audit quality and audit committee variables have no significant effect on tax avoidance. Keywords: Tax avoidance, Proportion of Independent Commisioners, Institutional Ownership, Audit Quality, Audit Committee, corporate governance